A Terrifying Manipulator of Signs. Issue 2 (May 2020) - Svirsky, Marcelo; Ben-Arie, Ronnen
Abstract : The question of Palestine has remained the ultimate test for intellectual and political consistency. In this article we canvass the discrepancies between two opposing French intellectual traditions in relation to Palestine, and scrutinise them in relation to Israel's investments in political languages designed for external constituencies. The article concludes with an observation on how French feminist voices are today shaping the conversation about the Palestine question in progressive ways.